1998
DOI: 10.1016/s0925-4773(97)00188-3
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in microphthalmia, the mouse homolog of the human deafness gene MITF, affect neuroepithelial and neural crest-derived melanocytes differently

Abstract: The mouse microphthalmia (Mitf) gene encodes a basic-helix-loop-helix-zipper transcription factor whose mutations are associated with abnormalities in neuroepithelial and neural crest-derived melanocytes. In wild type embryos, Mitf expression in neuropithelium and neural crest precedes that of the melanoblast marker Dct, is then co-expressed with Dct, and gradually fades away except in cells in hair follicles. In embryos with severe Mitf mutations, neural crest-derived Mitf-expressing cells are rare, lack Dct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
175
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(187 citation statements)
references
References 33 publications
10
175
2
Order By: Relevance
“…Baxter et al reported that SLC45A2 is expressed in pigment precursor cells during embryonic development and that its protein expression pattern is similar to those of the melanin-producing enzyme dopachrome tautomerase (DCT) and tyrosinase-related protein 1 (TYRP1), suggesting that this gene is like-wise dependent on microphthalmia-associated transcription factor (MITF), as in the retinal pigment epithelium [18]. However, the expression of SLC45A2 in early neural crest-derived melanocytes is similar to that of DCT, but not TYR or TYRP1 [19]. SLC45A2 has thus served as new marker of the migratory melanoblast population, which previously could only be identified by the co-expression of DCT, MITF and KIT.…”
Section: Slc45a2 Was Originally Identified As An Antigen Recognized Bmentioning
confidence: 99%
“…Baxter et al reported that SLC45A2 is expressed in pigment precursor cells during embryonic development and that its protein expression pattern is similar to those of the melanin-producing enzyme dopachrome tautomerase (DCT) and tyrosinase-related protein 1 (TYRP1), suggesting that this gene is like-wise dependent on microphthalmia-associated transcription factor (MITF), as in the retinal pigment epithelium [18]. However, the expression of SLC45A2 in early neural crest-derived melanocytes is similar to that of DCT, but not TYR or TYRP1 [19]. SLC45A2 has thus served as new marker of the migratory melanoblast population, which previously could only be identified by the co-expression of DCT, MITF and KIT.…”
Section: Slc45a2 Was Originally Identified As An Antigen Recognized Bmentioning
confidence: 99%
“…In the mouse, MITF mutations result in a reduction of absolute numbers of melanocyte precursor cells (Hornyak et al, 2001). In contrast, retinal pigment epithelial cells (RPE) that are not neural crest in origin survive severe MITF mutations (Nakayama et al, 1998), albeit without pigment and with evidence of hyperproliferation and neuroretinal transdifferentiation.…”
Section: Mitf-m Is Critical For the Melanocyte Fate In The Neural Crementioning
confidence: 99%
“…Disruption of either gene or their upstream regulator ␤-catenin in mouse RPE results in transdifferentiation of the RPE into neural retina-like tissues (12)(13)(14). The critical role of OTX2 in RPE development is well documented (12,15).…”
mentioning
confidence: 99%